Does Quality of Financial Statement Affected by Internal Control System and Internal Audit? - Kewo, Cecilia Lelly; Afiah, Nunuy Nur (International Journal of Economics and Financial Issues, 2017)
The purpose of this study to examine and analyze the influence internal control systems and internal audit to financial statement quality of local government. Usefulness of research as input for local government to improve implementation internal control, effectiveness of the internal audit function and improve quality of financial reports. Data conducted by taking 66 local government unit tool of the 15 districts and city in Indonesia. Analysis data study using path analysis. The conclusion is internal control system and internal audit partially and simultaneously have positive effect on the quality of financial statements. Keywords: internal control systems, internal audit function, financial statement quality JEL Classifications: G2, M4